Internet of things-based smart facilities management services successful implementation instrument development, validity, and reliability - Sidek, Norliza; Ali, Nor'ashikin; Rosman, Romzie (IEEE Computer Society, 2020)
The purpose of Internet of Things-based Smart Facilities Management Services (IoTbSFMS) is to increase the efficiency and effectiveness of facilities management services through improvement and innovation. Despite a common understanding that individual technology readiness and overall quality is an essential element in IoT-based technology success, there is a dearth of theoretical and empirical research on these elements as a facilitator of successful IoTbSFMS implementation. This study develops the IoTbSFMS validated instrument and proposes an integrated approach of instrument development through a multi-stage technique and rigorous statistical testing. Thirteen IoT experts had evaluated the content validity where two measurement items were excluded as per expert review's suggestion, which remaining 11 constructs and 58 measurement items. The process was followed by a pre-test assessment to determine the effectiveness of the measurement items. Finally, a pilot study assessment was conducted among 33 respondents. The collected data were analysed using SPSS25, Smart-PLS, and JASP software. As a result, the Content Validity Index (CVI) for the final IoTbSFMS constructs and items was deemed acceptable (CVI =0.82). The internal consistency reliability of the measurement instruments showed that the Cronbach's alpha and McDonald's omega for independent variables ranged from 0.682 to 0.989 and 0.685 to 0.989. These values suggest that all the constructs had acceptable validity and reliability. This paper contributes in encouraging researchers to look beyond the traditional approach in measuring the internal consistency reliability of the measurement instruments.